Metode wasatiyyah sharh al-Nawawi dan al-Mubarakfuri terhadap Ahadith Mutasyabihat dalam Sahih Muslim: Kajian sikap agamawan di Kuala Terengganu, Terengganu / Mohd Faiz Hakimi Mat Idris - Mohd Faiz Hakimi, Mat Idris (2016)

(untitled)
This research was conducted to explore how al-Nawawi and al-Mubarakfuri interpreted mutasyabihat ahadith in the Sahih Muslim. The research was conducted through a comparison of the sharh methods used by al-Nawawi and al-Mubarakfuri. 29 mutasyabihat ahadith were identified. Out of these 29 texts, 14 were in the dhatiyyah category, 8 were in the actions category, and 7 were in the feelings category. There are a few things in common between al-Nawawi and al-Mubarakfuri‟s wasatiyyah methods. Both scholars referred to verses from the Qur‟an, the ahadith, and the opinions of Islamic scholars, and both also studied the language and balaghah of the texts. However, only al-Nawawi referred to gharib al-hadith and Qira‟at experts, while only al-Mubarakfuri specifically referred to historical texts. Their approach to matters pertaining to the sanad of the ahadith, which is the compiling of biographical information on the narrators of the ahadith, and their definitions of the term riwayah are also similar. While only al-Nawawi defined the terms haddathana, „an, and rafa‟ah, both scholars mentioned fiqh al-hadith. Both scholars also provided methods, guidelines, and summaries of the texts, and issued rulings from them. Discussions on these mutasyabihat ahadith suggest that neither one of the scholars were tied to any specific school of tafsir. However, al-Nawawi was more inclined to refer to al-Ta‟wil, while al-Mubarakfuri had a higher level of detachment. Their methods of sharh, or their approach in the expounding of the mutasyabihat ahadith encourages harmony, tolerance, openness, and a manhaj that is moderate. The results of a field study involving 200 samples indicate that the negative attitudes of the respondents were at a low level, whereas the positive attitudes of the respondents were at a high level. A chi-square test shows that there was a significant relationship between the respondents‟ academic specialization and their openness, selflessness, optimism, curiosity, fanatical tendencies, franticness, and rigidness. Results also show that there was no significant correlation between the respondents‟ academic specialization and their feelings of concern, their resoluteness, pragmatism, indifference and impassiveness. These results reflect the attitudes of local religious leaders in Kuala Terengganu who are mostly moderate when it comes to issues related to mutasyabihat ahadith.